Open innovation policy for small and medium enterprises in Hanoi city - Nguyen Huy Cong; Le Hung Lan; Nguyen Hoang Hai (Journal SCIENCE AND TECHNOLOGY POLICIES AND MANAGEMENT, 2025)
Small and Medium Enterprises (SMEs) play an important role in the economy of every country, not only because they represent a large proportion of the total number of businesses but also due to their flexibility and contribution to economic development. SMEs typically account for a large share of total businesses, generate numerous jobs, and make significant contributions to the local and national GDP. This paper explores and quantifies the factors affecting open innovation in SMEs. The research team adopts an innovation approach from the supply-demand perspective, using a mixed-methods approach that combines qualitative and quantitative analysis, based on a survey of 38 businesses operating in Hanoi, Vietnam. The research findings show that all eight initially proposed factors have a positive impact on open innovation in businesses in Hanoi. Among these, the factors of financial resources (FR), competitive market (CM), and research and development (R&D) have the greatest impact on open innovation in SMEs in Hanoi. Based on these findings, the author proposes several breakthrough policy solutions to enhance open innovation in SMEs in Hanoi in the coming period. Code: 24110401